The dominant model of meat production and consumption as a socially acute question for activist education - Cabello-Garrido, Aurelio; Cebrián-Robles, Daniel; España-Ramos, Enrique; González-García, Francisco José; Cruz-Lorite, Isabel María; España-Naveira, Paloma; Blanco-López, Ángel (Springer, 2023)
Public debate often centers on issues that affect our lives and which reflect interests of various social groups and scientific communities, leading to controversies about what we may call socially acute questions (SAQs). In this paper we focus on two SAQs linked to the dominant model of meat production and consumption in Western countries, namely its impact on the environment and the health problems associated with high-meat diets. Given the importance of education in relation to these SAQs, our main objectives here were to examine the extent to which a Cartography of Controversy (CoC) approach is a useful tool for exploring and visualizing the views and ideas of preservice teachers about the controversies associated with this model of meat production and consumption, and to compare their initial maps with our own, one that is informed by a more detailed socioepistemological analysis. As a complement to this inquiry, we also present the SAQ–Eating Meat project, the aim of which is to encourage citizens to reflect on how food production and consumption may impact health and the environment, and then to take action toward change. In comparison with our own map, those produced by students did not reflect the full complexity of the controversies surrounding the dominant model of meat production and consumption, and some actants were missing. The results nevertheless suggest that a CoC approach is a useful way of engaging students with SAQs and that it offers them a framework in which to extend their inquiry and knowledge, providing a platform from which they may move toward taking action for change.
Keywords: Debates - Estudio y enseñanza; Carne - Consumo - Aspectos ambientales; Cambios climáticos; Socially acute questions; Cartography of controversy; Climate crisis; Noncommunicable diseases; Meat